A high-performance ceramic composite anode for protonic ceramic fuel cells based on lanthanum strontium vanadate - Song, Sang-Hyun; Yoon, Sung-Eun; Choi, Jaewon; Kim, Byung-Kook; Park, Jong-Sung (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The composite electrodes for protonic ceramic fuel cells (PCFC) were fabricated by infiltration of (La0.8Sr0.2)FeO3-delta (LSF) cathode and (La0.7Sr0.3)V0.90O3-delta (LSV) anode into a porous protonic ceramic, Ba(Ce0.51Zr0.30Y0.15Zn0.04)O3-delta (BCZY-Zn), respectively. Further, Pd-ceria catalysts were added into the composite anode. In the same method, the oxygen ion conducting fuel cells with the yttria-stabilized zirconia as an electrolyte (YSZ cell) were also fabricated. At 973 K, the non-ohmic area specific resistance (ASR) of PCFC (0.09 Omega cm(2)) was much smaller than that of the YSZ cell (0.28 Omega cm(2)) although the protonic conductivity of BCZY-Zn was slightly smaller than the oxygen ion conductivity of YSZ. According to the analysis of the symmetric cells with BCZY-Zn as an electrolyte, the LSV-composite anode showed better performance than the LSF-composite cathode at low temperatures. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: BA0.5SR0.5ZN0.2FE0.8O3-DELTA PEROVSKITE CATHODE; CONDUCTING ELECTROLYTES; SOFC CATHODES; STABILITY